Gynecological conditions related to the perianal area and coloproctology - Aleksey A. Khryanin; Daniil R. Markaryan; Mikhail A. Agapov; Valentina K. Bocharovav (IP Berlin A.V., 2021)
This review is addressed to the specialists who treat and correct pathologies of the perianal area and pelvic floor. The pelvic floor area is a space in which the organs of different systems have a common origin and a common framework, therefore they are located in close contact with each other. In view of these features, all specialists working with pelvic floor dysfunction should be aware of the possible combination with disorders from neighboring organs and systems. The article discusses the most urgent and common proctological and urological problems of pregnant women and maternity women, including perineal damage during vaginal childbirth with the development of anal incontinence and urinary incontinence, rectocele, prolapse and prolapse of pelvic organs. The paper presents a detailed description of all anatomical structures involved in the pathological process, as well as their gradual embryonic development. The article presented in details the disorders, which are lying in the base of pelvic organ dysfunctions, from the point of view of modern anatomical data, and discussed different diagnostic protocols and tactical approaches to the choice of treatment. Special attention is paid to the points of interaction of related specialists (urologists and proctologists) and the need for their joint participation in the medical and diagnostic process. Colorectal surgeons should be aware of the frequently associated gynecological pathologies described in this article. The cooperation of related specialists in the field of working with pelvic floor pathology is necessary to exchange experience and improve the quality of care for this category of patients. The article is illustrated with original drawings and clinical examples before and after.